Characterization of the Electrophysiologic Remodeling of Patients With Ischemic Cardiomyopathy by Clinical Measurements and Computer Simulations Coupled With Machine Learning - Aronis, Konstantinos N.; Prakosa, Adityo; Bergamaschi, Teya; Berger, Ronald D.; Boyle, Patrick M.; Chrispin, Jonathan; Ju, Suyeon; Marine, Joseph E.; Sinha, Sunil; Tandri, Harikrishna; Ashikaga, Hiroshi; Trayanova, Natalia A. (Frontiers in Physiology, 2021)
Rationale: Patients with ischemic cardiomyopathy (ICMP) are at high risk for malignant arrhythmias, largely due to electrophysiological remodeling of the noninfarcted myocardium. The electrophysiological properties of the noninfarcted myocardium of patients with ICMP remain largely unknown. Objectives: To assess the pro-arrhythmic behavior of non-infarcted myocardium in ICMP patients and couple computational simulations with machine learning to establish a methodology for the development of disease-specific action potential models based on clinically-measured action potential duration restitution (APDR) data. Methods and Results: We enrolled 22 patients undergoing left-sided ablation (10 ICMP) and compared APDRs between ICMP and structurally normal left ventricles (SNLV). APDRs were clinically assessed with a decremental pacing protocol. Using genetic algorithms, we constructed populations of action potential models that incorporate the cohort-specific APDRs. The variability in the populations of ICMP and SNLV models was captured by clustering models based on their similarity using unsupervised machine learning. The pro-arrhythmic potential of ICMP and SNLV models was assessed in cell- and tissue-level simulations. Clinical measurements established that ICMP patients have a steeper APDR slope compared to SNLV (by 38%, p<0.01). In cell-level simulations, electrical alternans were induced in ICMP models at a longer cycle length compared to SNLV models (385-400 ms vs. 355 ms). In tissue-level simulations, ICMP models were more inducible for sustained functional re-entry compared to SNLV models. Conclusions: Myocardial remodeling in ICMP patients is manifested as a steeper APDR compared to SNLV, which underlies the greater arrhythmogenic propensity in these patients, as demonstrated by cell- and tissue-level simulations using action potential models developed by genetic algorithms from clinical measurements. The methodology presented here captures the uncertainty inherent to genetic algorithms model development and provides a blueprint for use in future studies aimed at evaluating electrophysiological remodeling resulting from other cardiac disease.